2022
DOI: 10.3390/cells11142189
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Model for Cell Cycle Control in Which CDKs Act as Switches of Disordered Protein Phase Separation

Abstract: Cyclin-dependent kinases (CDKs) are presumed to control the cell cycle by phosphorylating a large number of proteins involved in S-phase and mitosis, two mechanistically disparate biological processes. While the traditional qualitative model of CDK-mediated cell cycle control relies on differences in inherent substrate specificity between distinct CDK-cyclin complexes, they are largely dispensable according to the opposing quantitative model, which states that changes in the overall CDK activity level promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Previous studies had shown that Xenopus CAP-H is phosphorylated in a mitosis-specific manner in Xenopus egg extracts ( Hirano et al, 1997 ; Kimura et al, 1998 ), and that Xenopus and human CAP-H can be phosphorylated by cyclin B-Cdk1 in vitro ( Kimura et al, 1998 ; Kimura et al, 2001 ; Shintomi et al, 2015 ). Whereas hCAP-H has three SP sites and one TP site in its N-tail ( Figure 2—figure supplement 1A ), it is known that Cdk1 phosphorylation is not exclusively proline directed ( Brown et al, 2015 ; Suzuki et al, 2015 ; Krasinska and Fisher, 2022 ). Moreover, a phospho-proteomic analysis identified phosphorylation at both SP/TP and non-SP/TP sites in this region ( Hornbeck et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had shown that Xenopus CAP-H is phosphorylated in a mitosis-specific manner in Xenopus egg extracts ( Hirano et al, 1997 ; Kimura et al, 1998 ), and that Xenopus and human CAP-H can be phosphorylated by cyclin B-Cdk1 in vitro ( Kimura et al, 1998 ; Kimura et al, 2001 ; Shintomi et al, 2015 ). Whereas hCAP-H has three SP sites and one TP site in its N-tail ( Figure 2—figure supplement 1A ), it is known that Cdk1 phosphorylation is not exclusively proline directed ( Brown et al, 2015 ; Suzuki et al, 2015 ; Krasinska and Fisher, 2022 ). Moreover, a phospho-proteomic analysis identified phosphorylation at both SP/TP and non-SP/TP sites in this region ( Hornbeck et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had shown that Xenopus CAP-H is phosphorylated in a mitosis-specific manner in Xenopus egg extracts (Hirano et al , 1997; Kimura et al , 1998), and that Xenopus and human CAP-H can be phosphorylated by cyclin B-Cdk1 in vitro (Kimura et al , 1998; Kimura et al , 2001; Shintomi et al , 2015). Whereas hCAP-H has three SP sites and one TP site in its N-tail (Fig EV3A), it is known that Cdk1 phosphorylation is not exclusively proline-directed (Brown et al , 2015; Suzuki et al , 2015; Krasinska & Fisher, 2022). Moreover, a phospho-proteomic analysis identified phosphorylation at both SP/TP and non-SP/TP sites in this region (Hornbeck et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with their unique ability to interact with multiple partners, IDPs occupy hub positions in the scale-free network and play critical biological roles including transcriptional regulation [ 44 , 45 , 46 ]. Furthermore, they also regulate several key processes such as cell cycle regulation and facilitate phenotypic plasticity [ 47 , 48 , 49 , 50 ]. Nevertheless, IDP dysregulation of expression can often bring about non-specific interactions and generate phenotypic plasticity due to PIN modulation.…”
Section: Systems Biology In Cancermentioning
confidence: 99%